1996
DOI: 10.1093/clinids/22.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media and Mastoiditis Due to Mycobacterium fortuitum: Case Report, Review of Four Cases, and a Cautionary Note

Abstract: Mycobacterium fortuitum is a rarely reported cause of otitis media and mastoiditis. We report such a case recently seen at our institution and review the four previously published cases of this disease entity. Amikacin is recommended in the current medical literature as empirical treatment of disease due to M. fortuitum, but the isolate from our patient showed high-level resistance to amikacin, which is rare in clinical isolates of this species; this resistance was probably related to prior treatment with topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…We, as well as others [9,13], observed persistent drainage and the development of chronic ulcerations without tenderness or swelling. In contrast, tenderness, swelling and fever have been described in cases of prosthetic infections by M. fortuitum [16].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We, as well as others [9,13], observed persistent drainage and the development of chronic ulcerations without tenderness or swelling. In contrast, tenderness, swelling and fever have been described in cases of prosthetic infections by M. fortuitum [16].…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, tenderness, swelling and fever have been described in cases of prosthetic infections by M. fortuitum [16]. Fever has been observed in localized [5] and disseminated [13] infections, but patients undergoing NTM infections may also remain afebrile [5,9]. Febrile temperatures and an elevation of leukocyte counts have been reported in cases of sternal wound infections due to M. fortuitum where routine cultures grew normal skin flora [3], suggesting that mixed infections may explain the appearance of tenderness, redness and fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also reported that surgery alone for more serious wound infections, without antimicrobial therapy, was followed by healing but that relapse often occurred within 4 to 6 weeks of the surgery. In contrast, surgical excision and/or debridement of the wound site combined with appropriate antimicrobial therapy resulted in healing without relapse (131,194,203,205). Likewise, when a foreign body such as breast implant, percutaneous catheter, etc., is involved, removal of the foreign body appears to be essential to recovery (38,41,97,185,196).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Only a few cases of M. fortuitum chronic otitis media or mastoiditis have been reported (2,43,131). The earliest report of otitis media due to M. fortuitum was described by Austin and Lockey (2).…”
Section: Miscellaneous Diseasesmentioning
confidence: 99%